The Rasch Model Analysis of Secondary School Teachers' Acceptance of STEM Implementation in Teaching and Learning in Labuan - Bin Amatan, Mohammad Azri; Han, Crispina Gregory K.; Pang, Vincent (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This study aims to assess the acceptance of the implementation of STEM approaches in teaching and learning by secondary school teachers in the Federal Territory of Labuan. This study uses a quantitative assessment approach of a sample survey type. Data were collected through the STEM Implementation Acceptance Questionnaire involving 314 teachers who were randomly selected from nine secondary schools. Rasch model data analysis using WINSTEPS Version 3.69.1 software was applied to produce a Wright Map to measure the acceptance aspects of STEM implementation through the study questionnaire items. The results of the study showed that items that were difficult to accept included making quantitative predictions (measure > 1 logit), reducing exam stress, and developing a problem-solving model, while items that were easy to accept were fostering positive values, early planning, and various teaching and learning methods (measure < -1 logit). The component of teacher belief in STEM recorded the highest mean measure value (0.43 logit), followed by attitude (-0.30 logit) and teacher commitment (-0.11 logit). Teachers were more likely to accept the aspects of attitude and commitment than belief in the importance of STEM. The findings of this study provide an overview of the strengths and weaknesses of teachers' acceptance of STEM implementation in teaching and learning, which should be taken into account to increase teachers' confidence, attitude, and commitment towards the implementation of STEM in secondary schools.